Comparison of Glycomacropeptide with Phenylalanine Free-Synthetic Amino Acids in Test Meals to PKU Patients: No Significant Differences in Biomarkers, Including Plasma Phe Levels - Kirsten K. Ahring; Allan M. Lund; Erik Jensen; Thomas G. Jensen; Karen Brøndum-Nielsen; Michael Pedersen; Allan Bardow; Jens Juul Holst; Jens F. Rehfeld; Lisbeth B. Møller (Journal of Nutrition and Metabolism)
Introduction. Management of phenylketonuria (PKU) is achieved through low-phenylalanine (Phe) diet, supplemented with low-protein food and mixture of free-synthetic (FS) amino acid (AA). Casein glycomacropeptide (CGMP) is a natural peptide released in whey during cheese-making and does not contain Phe. Lacprodan® CGMP-20 used in this study contained a small amount of Phe due to minor presence of other proteins/peptides. Objective. The purpose of this study was to compare absorption of CGMP-20 to FSAA with the aim of evaluating short-term effects on plasma AAs as well as biomarkers related to food intake. Methods. This study included 8 patients, who had four visits and tested four drink mixtures (DM1–4), consisting of CGMP, FSAA, or a combination. Plasma blood samples were collected at baseline, 15, 30, 60, 120, and 240 minutes (min) after the meal. AA profiles and ghrelin were determined 6 times, while surrogate biomarkers were determined at baseline and 240 min. A visual analogue scale (VAS) was used for evaluation of taste and satiety. Results. The surrogate biomarker concentrations and VAS scores for satiety and taste were nonsignificant between the four DMs, and there were only few significant results for AA profiles (not Phe). Conclusion. CGMP and FSAA had the overall same nonsignificant short-term effect on biomarkers, including Phe. This combination of FSAA and CGMP is a suitable supplement for PKU patients.